Review of Five-Level Front-End Converters for Renewable-Energy Applications - Monteiro, Vitor; Tashakor, Nima; Sousa, Tiago J. C.; Kacetl, Tomas; Götz, Stefan; Afonso, Joao L. (Frontiers in Energy Research, 2020)
With the objective of minimizing environment and energy issues, distributed renewable-energy sources have reached remarkable advancements along the last decades, with special emphasis on wind and solar photovoltaic installations, which are deemed as the future of power generation in modern power systems. The integration of renewable-energy sources into the power system requires the use of advanced power electronic converters, representing a challenge within the paradigm of smart grids, e.g., to improve efficiency, to obtain high power density, to guarantee fault tolerance, to reduce the control complexity, and to mitigate power-quality problems. This paper presents a specific review about front-end converters for renewable-energy applications (more specifically the power inverter that interfaces the renewable-energy source with the power grid). It is important to note that the objective of this paper is not to cover all types of front-end converters; the focus is only on single-phase multilevel structures limited to five voltage levels, based on a voltage-source arrangement and allowing current or voltage feedback control. The established review is presented considering the following main classifications: (a) number of passive and active power semiconductors; (b) fault tolerance features; (c) control complexity; (d) requirements of specific passive components as capacitor or inductors; and (e) number of independent or split dc-link voltages. Throughout the paper, several specific five-level front-end topologies are presented and comparisons are made between them, highlighting the pros and cons of each one of them as a candidate for the interface of renewable-energy sources with the power grid.